Optimal Forestry Model Control with Logging and Tourism Factors - Aji Pratama, Mochammad Andhika (iora, 2020)
Forest is one of the natural resources that need to be preserved because it has vital functions for humans both ecologically and economically. In this study, a mathematical model of forestry dynamics was developed by dividing the forest area, indigenous people, non-indigenous people, population pressure and economic incentives. The model was analyzed by dynamic system theory, the existence of equilibrium points and their stability were determined. Using the second Lyapunov method, global stability was also determined. In that forestry model, logging and tourism factors were added which affect the dynamics of forest biomass. The Pontryagin maximum principle was used to obtain optimal conditions from the model. Numerical simulation shows that the use of forests by logging and tourism, reduces the amount of forest biomass, but the forest remains sustainable. Utilization of forests bycontrols will maximize the benefits of logging and tourism in the associated forests.